FEMINIST MESSAGES IN GURU DUTT’S PYAASA (1957): A DISTINCTIVE CASE STUDY - Bhattacharjee, Sunayan; Chakraborty, Amrita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Guru Dutt’s masterpiece Pyaasa (1957) is not just a movie. It is in fact much more than that. It is an experiment with humanity. It is also a journey along the brighter and darker alleys of the normal human mind. While dissecting everything that cripples the Indian society then and even now, it’s partly haunting and partly reassuring narrative makes us ask some fundamental questions vis-à-vis our social existence. One of the resultant questions that crops up in the process tries to uncover the true essence of womanhood. From the narcissistic and decidedly selfish character of Meena, played by the inimitable Mala Sinha, to the selfless and deeply loving character of Gulabo, enacted flawlessly by the mesmerizing Waheeda Rehman, the movie refuses to take sides and declare loyalties. While one might argue that the protagonist Vijay, played by Guru Dutt himself, sides towards Gulabo at the end of the movie, the inclination is far from being decisive. If one takes a clear look at the diegesis of the movie, she/ he would be able to appreciate that the decision is influenced more by convenience than by ideology. While ideology does play a part in what the movie theorizes, it is more of a reflection on the true nature of the society that we live in. This research paper makes an honest attempt at deciphering the obvious and subtle feminist messages that are ingrained in the movie. While doing so, the researcher looks not just at the narrative of the movie but at the filmmaking style as well for style often determines the ideological stance of any audiovisual material. While studying the given subject, the researcher uses the Auteur Theory, the Apparatus Theory, and the Feminist Film Theory.